(untitled) (International Journal of Food and Nutritional Sciences, 2022)
During the Covid -19 pandemic, educational institutions began offering online classes. Things gradually returned to normal. Traditional education has begun in educational institutions. So many teaching institution employees and their work-life balance are influenced by these two modes. This study is an attempt of analysing the impact of various factors such as employee’s gender, age, occupation, annual income, working hours, over time work, personal life, weekend work, work on vacation, sleeping hours, job priority, family priority, spouse profession, family cooperation on work life balance.